Blood component therapy for dry eye disease: a systematic review and network meta-analysis - Yu Zhang; Ning Li; Ziying Ge; Fang Li (Frontiers in Medicine)
ObjectiveBlood component therapy has shown promising potential as an emerging treatment for dry eye disease; however, it remains unclear which specific blood component is the most effective. This study aims to compare the efficacy of different blood components in the treatment of dry eye disease through a network meta-analysis, with the goal of providing the latest and most reliable evidence for clinical practice.MethodsWe conducted a systematic search of the PubMed, Web of Science, Cochrane, Embase, and Scopus databases, with the search concluding on June 1, 2024. Two independent researchers performed literature screening, data extraction, and quality assessment.ResultsA total of 16 randomized controlled trials (RCTs) involving 898 patients with dry eye disease were included. Six different blood components were utilized in treating dry eye disease, with platelet-rich plasma (PRP) being the most widely used. The results of the network meta-analysis indicated that platelet-rich plasma eye drops (PRPD) significantly outperformed artificial tears (AT) in improving the corneal fluorescein staining score (CFSS), while autologous serum (ALS) and umbilical cord serum (UCS) also demonstrated significantly better effects than AT in enhancing tear break-up time (TBUT). Additionally, ALS, PRP injection (PRPI), and PRPD showed significantly superior outcomes compared to AT in improving the ocular surface disease index (OSDI). However, no statistically significant differences were found among the various treatment modalities regarding their effects on Schirmer’s I value, CFSS, TBUT, and OSDI. SUCRA analysis predicted that UCS was the most effective in improving Schirmer’s I value and TBUT, while PRP excelled in enhancing CFSS and OSDI. Limitations such as publication bias and issues related to randomization, allocation concealment, and blinding may affect the reliability of the current findings.ConclusionBlood component therapy can significantly improve the pathological damage and ocular surface health in patients with dry eye disease. For those with aqueous-deficient dry eye, UCS may represent the optimal treatment option. In contrast, for patients with more severe corneal epithelial damage, PRP may offer a more effective therapeutic approach.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024534091.